Reducing radiation exposure with iterative reconstruction: an inter- and intra-scanner analysis. (26th October 2017) - Rohr, Aaron; Wick, Jo; Hill, Jacqueline; Walter, Carissa; Irani, Neville; Best, Shaun; Miller, Kirk; Ash, Ryan
Abstract: Our purpose in this study was to compare delivered radiation exposure via computed tomography dose index volume (CTDIvol ) and dose length production (DLP) measurements from computed tomography (CT) examinations performed on scanners with and without image-quality enhancing iterative reconstruction (IR) software. A retrospective analysis was conducted on randomly selected chest, abdomen, and/or pelvis CT examinations from three different scanners from 1 January 2013 to 31 December 2013. CTDIvol and DLP measurements were obtained from two CT scanners with and one CT scanner without IR software. To evaluate inter-scanner variability, we compared measurements from the same model CT scanners, one with and one without IR software. To evaluate intra-scanner variability, we compared measurements between two scanners with IR software from different manufacturers. CT scanners with IR software aided in the overall reduction in radiation exposure, measured as CTDIvol by 30% and DLP by 39% when compared to a scanner without IR. There was no significant difference in CTDlvol or DLP measurements across different manufacturers with IR software. As a result, IR software significantly decreased the radiation exposure to patients, but there were no differences in radiation measurements across CT manufacturers with IR software.